The Manila Harbor Forts 1942 - Black, James Jr (Philippine Studies, 1988)
This article covers not only Corregidor but also its three outpost forts at the entrance of Manila Bay, which together with Fort Wint on Grande Island in Subic Bay were collectively known as the harbor forts of Manila and Subic Bays. The four islands, are first Fort Mills, Corregidor Island, only kilometers from Bataan and the largest of the coast defense artillery. Second is Fort Hughes on Caballo Island, just 1 1/2 kilometers south of Corregidor and the last to be completed. Third is Fort Frank on Carabao Island, some 12 kilometers south of Corregidor and only 700 meters from the Cavite mainland. Last but not least is tiny Fort Drum on El Fraile Island, otherwise known as "The Concrete Battleship." No other fort like it exists anywhere in the world. La Monja Island, west of Corregidor, remained the only island in the Bay that was not fortified.